The Mother’s Role in Mother-Child Relationship Among Adolescents with Unwanted Pregnancies - Noradila Mohamed Faudzi; Melati Sumari; Azmawaty Mohamad Nor; Norhafisah Abd Rahman (USIM Press, 2024)
Vol. 25 No. 2 (2021): Special Issue MASEC